Sepsis by escherichia coli of uncommon starting in patient with T and NK cell lymphoma - Noriega-Baella, Carlos (2020)
Sepsis occurs in the presence of an infectious focus; in this case by Escherichia coli (E. coli), that toxins  can cause severe damage to the organism's functionality and morphology, being worsened in patients with diseases that affect the immune system; as is this case in the presence of hematological malignancy. A 42-year-old female patient with a diagnosis of T-NK non-Hodgkin lymphoma presented with a necrotic plaque on the palate, temperature above 38 ° C, respiratory rate exceeding 20 breaths per minute, and heart rate exceeding 90 beats per minute. , on examination of a positive pharyngeal culture for E. coli, negative urine culture, confirming a pharyngeal infectious starting point; Treat with amikacin endovenously for 7 days with good response to antibiotic therapy. An infrequent case is reported for this type of bacteria in the oral area and a review of the subject.